Late Recurrence of Ovarian Cancer after 18 Years of Disease-Free Survival: A Case Report and Review of the Literature - Yoko Suzuki; Satoko Eguchi; Takahide Arimoto (Hindawi Limited, 2024)
We present a case of recurrent ovarian cancer at the age of 75, gravida 1 para 0, with 18 years of disease-free survival. Chemotherapy brought a 10-month partial response status; to further improve the overall survival, the patient was evaluated using the AGO score (DESKTOP III trial, 2020), which was originally intended for cases immediately after the diagnosis of recurrence; the score has indicated a significant outcome; the patient went through a hepatosplenic metastatic site resection; and complete resection was achieved. Subsequently, the PARP inhibitor was introduced, which has led to 14 months of disease-free survival. Fifteen cases of late recurrence of epithelial ovarian cancer have been reported and are summarized at the end of this paper.